Influência de fenômenos climáticos sobre o regime de vazões na bacia hidrográfica do rio Tapajós - SOUSA, Eduarda Silva de (2024)
The observation and analysis of the space-time variability of precipitation and hydrological phenomena play crucial roles in the responsible management of natural resources. Two global phenomena, the El Niño Southern Oscillation (ENSO) and the Atlantic Dipole, exert a significant influence on rainfall patterns and, consequently, on river flow. This study aimed to investigate how the climatic phenomena ENSO and the Atlantic Dipole affect available streamflows, using flow duration curves, in the sub-basins that make up the Tapajós River Basin (TRB). The statistical method of Pearson correlation was employed to study the relationship between streamflow and climate indices, thus revealing the influence of ENSO and the Atlantic Dipole on river flow in the TRB. In general, the analyses indicated that climatic phenomena such as ENSO and the Atlantic Dipole have a significant impact on river behavior. Most years with strong correlations between these phenomena coincided with the occurrence of higher streamflows.